Enunciative and pragmatic analysis of idiomatic expressions in political discourse (Cahiers Africains de rhétorique, 2025)
This research proposes an enunciative and pragmatic analysis of idiomatic expressions in political discourse. Idiomatic expressions, due to their fixed and culturally anchored aspect, are quite powerful linguistic tools used in political communication. Idiomatic expressions are not simply words; they are formidable weapons for any speaker seeking to establish their authority, persuade their audience, and create an emotional connection with them. By using these expressions, we can play with common references and implied meanings to captivate and influence the audience in a subtle way. These turns of phrase allow us to give color and depth to our speeches, adding a personal and authentic touch to our words. Through this study of political speeches, the objective is to understand and explain how idiomatic expressions contribute to influencing opinions and managing power relations between politicians and their people. This research has thus made it possible to identify discursive strategies employed by political leaders in specific political contexts.